Nitrogen recovery from fertilizers and cover crops by maize crop under no-tillage system - da Silva, Edson Cabral; Muraoka, Takashi; Bastos, Alefe Viana Souza; Franzini, Vinícius Ide; da Silva, Alinne; Buzetti, Salatiér [UNESP]; Sakadevan, Karuppan; Soares, Frederico Antonio Loureiro; Teixeira, Marconi Batista; Trivelin, Paulo César Ocheuze; de Araújo, Leandro Coelho [UNESP] (Southern Cross Publishing, 2020)
Crop rotation associated with the use of cover crops promotes the introduction of crop residues to the soil, with direct and indirect effects on the availability of plant nutrients, especially nitrogen (N). The objectives of this study were to estimate the N utilization from 15N-urea and cover crop residues (labelled with 15N) of maize crops grown in succession, and evaluate the effects of the isolated and combined use of cover crops and urea on maize plant height, yield components, and grain yield, grown under a no-tillage system. Field research was conducted in an Oxisol (Rhodic Haplustox), Cerrado (Savannah) phase. The experimental design was a randomized block with 20 treatments and four replications in a 5x4 factorial scheme. The treatments were four cover crops species: sunn hemp (Crotalaria juncea L.), pigeon pea (Cajanus cajan (L.) Millsp), green velvet bean (Mucuna prurens), and millet (Pennisetum glaucum L.) + spontaneous vegetation (fallow in the off-season), combined with four N rates: 0, 30, 90, and 150 kg ha-1, applied at the sowing and topdressing stages. The results showed that legume cover crops provided maize grain yields equivalent to the application of 80–108 kg ha-1 N as urea. The urea N utilization by the maize was at an average of 43.5 % of the applied amount. The results indicate that cover crops, particularly legume cover crops, are an important source of N to non-legume cereals. Legumes used as cover crops can replace nitrogen fertilizers of more than 80 kg ha, which is both environmentally and economically viable for corn production.
Keywords: green manure; isotope dilution; Oxisol; Savannah; urea; Zea mays